Development Of Nursing Care Instruments Based On The 3s Framework (Sdki, Slki, Siki) For Inpatient Settings - Aris Citra Wisuda; Citra Suraya; Miming Oxyandi; Isrizal (Citra Delima Scientific journal of Citra Internasional Institute, 2025)
Standardized nursing documentation is essential for ensuring consistency, accountability, and quality in patient care. In Indonesia, the 3S framework—comprising the Standar Diagnosa Keperawatan Indonesia (SDKI), Standar Luaran Keperawatan Indonesia (SLKI), and Standar Intervensi Keperawatan Indonesia (SIKI) serves as a national standard. However, its application in inpatient settings remains inconsistent due to the lack of integrated, user-friendly tools. This study aimed to develop and validate a nursing care documentation instrument based on the 3S framework to improve documentation accuracy, support clinical decision-making, and promote standardization in inpatient wards. A Research and Development (R&D) approach was employed, using a modified Borg and Gall model across five stages: preliminary study, planning, product development, expert validation, and limited field testing. Data were gathered through literature reviews, chart audits, clinical interviews, and focus group discussions with nurses. The instrument was designed to address the 12 most frequently encountered nursing diagnoses in general medical-surgical wards, which were systematically mapped to appropriate SLKI outcomes and SIKI interventions. The final tool features structured diagnosis formats (PES, PR, PS), outcome targets with timelines, and categorized interventions (observation, treatment, education, collaboration), implemented in a shift-based checklist format. Validation by five expert nurses yielded strong content validity (I-CVI range: 0.833–1.000), and field testing with 15 clinical nurses demonstrated acceptable internal consistency (KR-20: 0.790–0.845). Additionally, 87% of nurses reported improvements in documentation quality and workflow efficiency. In conclusion, the 3S-based nursing care instrument is valid, reliable, and practical for clinical use, and its adoption is recommended to enhance nursing documentation standards and the quality of care in hospital settings.